Posterior Decompression of Central, Lateral Recess, and Unilateral Foraminal Lumbar Spinal Stenosis by Semi-Circumferential Decompression and the Lateral Fenestration Technique - Lee, Young-Sang; Oh, Min-Young; Shin, Keun-Young (Journal of Korean Society of Spine Surgery, 2024)
Study Design: A retrospective study. Objectives: To analyze the clinical and radiographic results of the original posterior decompression-only technique (semi-circumferential decompression and lateral fenestration [SCD & LF]) for lumbar spinal stenosis. Summary of the Literature Review: The SCD technique that preserves the facet joints produces less postoperative instability and effectively reduces back pain and radiating pain in patients with central and lateral recess stenosis. Materials and Methods: 50 patients who were operated with posterior decompression only technique(SCD & LF), during the period from November, 2014 to September, 2022 were selected. Average follow up period was 19 months. Clinical change of back pain and radiating pain was evaluated by VAS score and ODI score one day before surgery and at the last follow-up. Radiographic change was evaluated by slip percentage, slip angle, dynamic translation and dynamic angulation. Results: The VAS scores for back pain and radiating pain substantially decreased from 7.1 and 7.0 to 2.9 and 3.4 at the last follow-up, respectively (p<0.01). The ODI scores decreased from 24.8 to 9.3 at the last follow-up (p<0.01). The slip percentage decreased from 4.24% to 4.12% (p>0.05), the slip angle increased from 6.44° to 7.09° (p>0.05), dynamic translation increased from 0.1 mm to 0.2 mm (p>0.05), and dynamic angulation decreased from 3.9° to 3.2° (p>0.05), but without statistically significant differences between the preoperative status and the last follow-up. Conclusions: SCD & LF for central, lateral recess and foraminal stenosis showed effectiveness in symptom relief and did not cause instability. KCI Citation Count: 0